Factors Impacting University Student Satisfaction in Flipped Classroom: A Case study of a Public University in Yunnan Province, China - Guo, YaoXu (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
Student satisfaction is an important factor to improve flipped classroom teaching effect. This study focuses on the effects of teacher-student interaction, student engagement, self-efficacy, support services and adoption intention on student satisfaction in flipped classroom. This study was conducted in a public university in Yunnan Province, with 332 students as the survey objects, and 30 students were selected to participate in strategic planning. The research adopts a mixed research method combining quantitative and qualitative. Quantitative data is obtained through questionnaire survey for statistical analysis, and qualitative data is obtained through interview survey for qualitative analysis. The results of multiple linear regression showed that teacher-student interaction (P < 0.001, β=0.3643), student engagement (P = 0.033, β=0.1218), self-efficacy (P = 0.01, β=0.1539), support service (P < 0.001, β=0.2095)had a significant positive correlation with flipped classroom student satisfaction, while adoption intention (P = 0.115, β=0.810) had no significant correlation with satisfaction. At the same time, the paired sample T-test and interview survey results of variable data before and after the strategic plan show that improving the quality of teacher-student interaction and student participation, improving students' self-efficacy, and optimizing learning support services will improve students' satisfaction with flipped classroom learning and improve the actual effect of flipped classroom.